Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00244-006-0170-8
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Bioaccessibility in a Soil Amended with Drinking-Water Treatment Residuals in the Presence of Phosphorus Fertilizer

Abstract: A laboratory incubation study was conducted to determine the effect of drinking-water treatment residuals (WTRs) on arsenic (As) bioaccessibility and phytoavailability in a poorly As-sorbing soil contaminated with arsenical pesticides and fertilized with triple super phosphate (TSP). The Immokalee soil (a sandy spodosol with minimal As-retention capacity) was amended with 2 WTRs (Al and Fe) at 5 application rates ranging between 0% and 5% wt/wt. Sodium arsenate and TSP were used to spike the soil with 90 mg As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…No significant relationship between the Pb bioaccessibility and CEC was also reported by some previous studies (Romero et al 2008;Sarkar et al 2007;Tang et al 2008). Soil OM has been showed to tightly bind Pb and played a vital role in determining Pb speciation in soils (Newton et al 2006;Pinheiro et al 1999).…”
Section: Factors In Controlling the Bioaccessibility Of Pb And Assupporting
confidence: 56%
See 1 more Smart Citation
“…No significant relationship between the Pb bioaccessibility and CEC was also reported by some previous studies (Romero et al 2008;Sarkar et al 2007;Tang et al 2008). Soil OM has been showed to tightly bind Pb and played a vital role in determining Pb speciation in soils (Newton et al 2006;Pinheiro et al 1999).…”
Section: Factors In Controlling the Bioaccessibility Of Pb And Assupporting
confidence: 56%
“…Another type is soil properties, such as soil pH, soil texture, soil organic matter (OM), Fe, and Mn oxides, etc. (Girouard and Zagury 2009;Sarkar et al 2007;Yang et al 2002). For example, soil pH is a main parameter determining the bioaccessibility, and bioaccessibility of Pb and As decreases with increasing pH.…”
mentioning
confidence: 99%
“…In the present study, the CMP is the most effective among the three phosphate amendments used to reduce the bioaccessibility of Pb. Sarkar et al (2007) found that the bioaccessibility of soil As in the human stomach was not influenced by the presence or absence of phosphate after considerable equilibration time (12 months). In the present study, the bioaccessibility of soil As did not change except for a small decrease for the treatment of CMP with the addition of phosphate in gastric and small intestinal phase.…”
Section: Bioaccessibility Of As and Pb In Soilmentioning
confidence: 96%
“…Oral bioaccessibility test, which is a measure of solubility of heavy metal in the gastrointestinal compartment, is applicable to the soil ingestion pathway (Beak et al 2006;Ruby et al 1996). The bioaccessibility of metal has also been used to evaluate the effectiveness of heavy metal remediation in soils (Bosso et al 2008;Sarkar et al 2007). Bosso's (2008) study showed that the most efficient phosphate source was NaH 2 PO 4 , which reduced Pb solubility by 92% in acidic gastric conditions after the first month.…”
Section: Introductionmentioning
confidence: 99%
“…The key contaminants included in this work are arsenic (As), lead (Pb) and cadmium (Cd) as they are potentially harmful to human health (ATSDR, 2007b;ATSDR, 2007a;ATSDR, 2008) and the most common elements undergoing bioaccessibility research Ruby et al, 1993;Ruby et al, 1996;Albores et al, 2000;Oomen et al, 2002;Marschner et al, 2006;Chan et al, 2007;Datta et al, 2007;Drexler and Brattin, 2007;Finzgar et al, 2007;Hansen et al, 2007;Juhasz et al, 2007aJuhasz et al, , 2007bLjung et al, 2007;Sarkar et al, 2007;Subacz et al, 2007;Turner and Ip, 2007;Van de Wiele et al, 2007;Beak et al, 2008;Moseley et al, 2008;Girouard and Zagury, 2009;Morman et al, 2009;Nagar et al, 2009;Poggio et al, 2009;Smith et al, 2009;Zhang et al, 2009;Demetriades et al, 2010;Juhasz et al2010). …”
Section: Introductionmentioning
confidence: 99%